Thymus Hyperplasia and Thymoma Type B in Patients with Myasthenia Gravis: Two case reports and Literature Review - Selman Dumani; Altin Kuqo; Ermal Likaj; Saimir Kuci; Majlinda Ikonomi; Laureta Dibra; Alessia Mehmeti; Ejona Celiku; Altin Veshti (Albanian Journal of Trauma and Emergency Surgery)
Introduction: The thymus gland plays a pivotal role in immune system regulation, but conditions such as thymic hyperplasia (TH) and thymoma pose distinct clinical challenges due to their rarity and complex presentation in surgical practice. Both conditions can mimic similar symptoms, particularly in patients with Myasthenia Gravis (MG), where surgery serves as both a diagnostic and therapeutic intervention. This report presents the surgical management and outcomes of two MG patients with distinct thymic pathologies: TH and Type B thymoma, alongside a review of the relevant literature.